Zmiany w planowaniu i zarządzaniu gospodarką narodową jako narzędzie intensyfikacji wzrostu gospodarczego ZSRR - Szczepański, Józef (Wydział Prawa i Administracji UAM, 1967)
In 1965/66 changes were started in the national economy of the USSR. The main purpose of these changes was to eliminate the many disproportions which had been growing for some time, and to create more advantageous conditions for intensifying economic growth. The changes in the USSR concern the fundamental economic proportions and organization of economy as well as the principles of planning nad management. Worthy of notice in the field or economic planning and management are the tendencies to strengthen central plannig with a simultaneous increase of decentralization elements in economic management. The result of these tendencies is the growth of autonomy of socialist enterprises which at present undertake the majority of socalled current decision of production such as volume and assortment of production, direction of supply and sales management of labour force and choice and method of production. The author indicates various factors which, in practice, limit, the autonomy of enterprises and further means indispensible for the widening of this autonomy. In connection with the growth of autonomy of socialist enterprises the coordination of the interest of the society as a whole with the activity of the enterprise is of great importance. The various economic means such as credit, prices, the tax system and the new measures of evaluating the efficiency of enterprises, as the real production of goods, size of profit and level of rentability, are becoming today the man instrument of this coordination. The analyses the functioning of economic means of State influence on production decisions of enterprises and the measures of evaluating the work of enterprises, and submits various postulates for their further improvement. In the article an attempt is made to evaluate the new system of economic stimulation and its role in the proces of intesifying economic growth. The last part of the article which consitiues about one third of the whole work, is a partial evaluation of the effectiveness of economic changes in planning and management of USSR economy, based on result from 704 enterprises, in which the new principle were introduced in 1966. These enterprises gained far better economic results in man activities s. g. in realizing production, level of rentability, labour efficiency etc. The proper functioning of an enterprise, however, acting on the new principles of plannig and management depends, to a great extent, on further improvement of these principles and expansion of economic reforms. The author discusses various postulates im this field put forth by economic theorists and practicians.
Changes in economic planning and management as an instrument for intensifying economic growth in the USSRr